2007
DOI: 10.1007/s00270-007-9035-4
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Manual Aspiration Embolectomy of Renal Vein Thrombosis Due to Acute Pyelonephritis

Abstract: We report the case of a 50-year-old man who presented to our institution with septic thrombosis of the renal vein which had not resolved despite several days of antibiotic therapy. Optimal restoration of renal vein flow was obtained by percutaneous manual aspiration embolectomy (PMAE) in this patient with contraindication to fibrinolytic therapy and surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Novelli et al [9] reported right renal vein thrombosis following acute cholecystitis and pyelonephritis as with our case SA was the causative organism. Harris et al [10] reported bilateral renal vein thrombosis from pyelonephritis but due to a Klebsiella species.…”
Section: Discussionsupporting
confidence: 69%
“…Novelli et al [9] reported right renal vein thrombosis following acute cholecystitis and pyelonephritis as with our case SA was the causative organism. Harris et al [10] reported bilateral renal vein thrombosis from pyelonephritis but due to a Klebsiella species.…”
Section: Discussionsupporting
confidence: 69%
“…Although it was used earlier than most other endovascular methods, its use was not widespread. Manual AT has been successfully used to remove thrombus in the thrombosed dialysis fistulas, lower extremity deep vein thrombosis with or without impending venous gangrene, renal vein thrombosis, and pulmonary embolism (11)(12)(13)(14)(15). Manual AT can solve some of the problems encountered with thrombolysis and surgical embolectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The primary patency and secondary patency at three months postoperatively were around 90%, which is in accordance with previous reports. 5,8,17 However, at 12 months postoperatively both primary patency and secondary patency showed significant decline. We supposed that it might be attributed to vascular intimal hyperplasia and patients’ poor compliance to postoperative anticoagulation therapy.…”
Section: Discussionmentioning
confidence: 92%